Extending the sunspot area series from Kodaikanal Solar Observatory - Jha, Bibhuti Kumar; Hegde, Manjunath; Priyadarshi, Aditya; Mandal, Sudip; Ravindra, B.; Banerjee, Dipankar (Frontiers in Astronomy and Space Sciences, 2022)
Kodaikanal Solar Observatory (KoSO) possesses one of the world’s longest and homogeneous records of sunspot observations that span more than a century (1904 – 2017). Interestingly, these observations (originally recorded in photographic plates/films) were taken with the same setup over this entire time period which makes this data unique and best suitable for long-term solar variability studies. A large part of this data, between 1921 – 2011, was digitized earlier, and a catalogue containing the detected sunspot parameters (e.g., area and location) was published in Mandal et al. (2017). In this article, we extend the earlier catalogue by including new sets of data between 1904 – 1921 and 2011 – 2017. To this end, we digitize and calibrate these new datasets, which include resolving the issue of random image orientation. We fix this by comparing the KoSO images with co-temporal data from Royal Greenwich Observatory. Following that, a semi-automated sunspot detection and automated umbra detection algorithm are implemented onto these calibrated images to detect sunspots and umbra. Additionally, during this catalogue updation, we also filled data gaps in the existing KoSO sunspot catalogue (1921 – 2011) by virtue of re-calibrating the ‘rouge’ plates. This updated sunspot area series covering nearly 115 years (1904 – 2017) is being made available to the community and will be a unique source to study the long-term variability of the Sun.